PENYELESAIAN HUKUM DALAM MALPRAKTIK MEDIK - Sumartini Dewi (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2014)
In providing legal assurance and protection for both health service providers or doctors and the receivers of health services or patients, a set of laws is required to be the sign for them. How is the legal resolution when there is a alleged malpractice performed by a doctor ? The Indonesian Medical Disciplinary Board is the authorized institution to determine the presence of error (alleged malpractice) performed by a doctor in applying the medical science and decide the sanction. In terms of the negligence performed by medical practitioners in their profession, it must be settled first through mediation. In this case, the health law and the doctrine of health services is as the norm of Lex spesialis.